The role of exercise in restoring executive function: a comparison of tobacco-exposed college athletes and sedentary students - Wang, Minjia; Wu, Shuya; Ma, Qian; Hu, Hao; Liu, Yanpei; Wang, Yaozheng; Zhan, Shitao; Liu, Dongsen; Girard, Olivier (Frontiers in Physiology, 2024)
IntroductionAs adolescent smoking rates rise, its impact on cognitive function has drawn greater attention. This study explores whether exercise can mitigate the negative effects of smoking on executive function in male college students.MethodsSixty male college students were divided into four groups (n = 15 each): sedentary smokers, sedentary nonsmokers, athletic smokers, and athletic nonsmokers. All participants completed the Eriksen flanker task, with prefrontal cortex activation measured using functional near-infrared spectroscopy. After the baseline test, all sedentary students engaged in 33 min of high-intensity interval training, followed by the same procedures as in the pre-test.ResultsIn the flanker task, college athletes exhibited superior executive function compared to sedentary students, with higher accuracy (p = 0.042), faster reaction times (p = 0.002), and more pronounced brain activation (p = 0.048). Post-exercise, reaction times improved significantly in sedentary groups (p < 0.05). Smoking impaired executive function both before and after exercise, with smokers showing lower accuracy (p < 0.001), slower reaction times (p < 0.001), and diminished brain activation (p < 0.001) compared to nonsmokers.DiscussionEngaging in acute aerobic exercise may improve executive function in sedentary smokers. Exercise may help mitigate smoking-related declines in executive function among college students.